Frauds In Nigerian Banks: Nature, Deep-Seated Causes, Aftermaths And Probable Remedies - Kingsley A., Adeyemo (Richtmann Publishing, 2012)
This paper is descriptive in nature and it examines the nature, causes, effects and remedy for bank frauds in Nigeria.In recent years, frauds in Nigeria banking sector seemed to have assumed a frightening dimension and to a large extent, theconfidence the general public reposes in it, is put in jeopardy. The ability of banks to promote growth and development in anyeconomy is a function of the extent to which financial transactions are carried out with trust, confidence and least risk. These nodoubt require a safe and sound banking practice which many of the banks in Nigeria today have despised to their own peril. Thisstudy leaned heavily on the Nigerian Deposit Insurance Corporation (NDIC) annual reports for data relating to total amountinvolved in frauds and forgeries, ten banks with the highest fraud cases and categories of bank staff involved in frauds andforgeries. The paper concludes that the battle for the preclusion, uncovering and retribution of fraud offenders must be fought ontwo extensive fronts: First is to reduce the temptation to commit fraud and second to increase the chances of detection. While apositive work environment will help to achieve the former, the latter can be achieved by sound internal control system.